A Suzaku X-ray study of the mixed-morphology supernova remnant Kes 69 and searching for its gamma-ray counterpart - Sezer, A.; Ergin, T.; Yamazaki, R.; Ohira, Y.; Cesur, N. (OXFORD UNIV PRESS, 2018)
Kes 69 is a mixed-morphology (MM) supernova remnant (SNR) that is known to be interacting with molecular clouds based on 1720 MHz hydroxyl (OH) maser emission observations in the northeastern and southeastern regions. We present an investigation of Kes 69 using similar to 67 ks Suzaku observation. The X-ray spectrum of the whole SNR is well fitted by a non-equilibrium ionization model with an electron temperature of kT(e) similar to 2.5 keV, ionization time-scale of tau similar to 4.1 x 10(10) cm(-3) s and absorbing column density of N-II similar to 3.1 x 10(22) cm(-2). We clearly detected the Fe-K alpha line at similar to 6.5 keV in the spectra. The plasma shows slightly enhanced abundances of Mg, Si, S, and Fe indicating that the plasma is likely to be of ejecta origin. We find no significant feature of a recombining plasma in this SNR. In order to characterize radial variations in the X-ray spectral parameters, we also analyse annular regions in the remnant. We investigate the explosive origin of Kes 69 and favour the core-collapse origin. Additionally, we report a lack of significant gamma-ray emission from Kes 69, after analysing the GeV gamma-ray data taken for about 9 yr by the Large Area Telescope on board Fermi. Finally, we discuss the properties of Kes 69 in the context of other interacting MM SNRs.
Keywords: ISM: individual objects: Kesteven 69 (G21.8-0.6); ISM: supernova remnants; X-rays: ISM; gamma-rays: ISM; AREA TELESCOPE OBSERVATIONS; CORE-COLLAPSE SUPERNOVAE; IC 443; EMISSION; DISCOVERY; SPECTRUM; EXPLOSION; EVOLUTION; HYDROGEN; MASERS; Astronomy & Astrophysics